Assessment of the Financial Status in Adult Diabetic Patients Attending the Diabetic Clinic in Bankura Sammilani Medical College, Bankura - Indu Padmey1 , Karan Jain2 , Arindam De3 , Abhishek Joshi4 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Introduction: Diabetes and its complications impose significant economic consequences on individuals,families, health systems and countries. People living with diabetes and their families feel the impact ofdiabetes most directly, often through the expenses of diabetes treatment and loss of family income whendiabetes interferes with work.Objective: To assess the financial status of adult diabetic patients attending the diabetic clinic of BankuraSammilani Medical College, Bankura.Materials and Method: It is an Institution based, Cross-sectional, descriptive Study. Complete enumerationof all patients attending Diabetic clinic of Bankura Sammilani Medical College and hospital, Bankura, WestBengal was done. Eligible consenting of adult patients (> 18 years of age) who were diagnosed as a caseof diabetes at least 1 year back and on treatment were interviewed with review of medical record and Outof pocket expenditure information was collected in terms of INR. It views the cost of NCDs as the sum ofseveral categories of direct and indirect costs. The study was preceded after obtaining ethical clearance.Data were entered in MS Excel spread sheet. Calculation was done with the help of software SPSS 22.0 freeversion.Results: Majority of annual treatment expenses of study subjects were in Drugs and consumables (66.73%)followed by Investigation cost 15.19% and others. The average INR for annual total diabetes care was13,733.17±13,389.86.Conclusion: Drugs and consumables, investigation and transportation cost leads to more than 90.0% of outof pocket expenditure causing financial burden on both adult diabetic patient and its family.